Proceedings of the 1st ACM SIGPLAN International Workshop on Machine Learning and Programming Languages 2017
DOI: 10.1145/3088525.3088564
|View full text |Cite
|
Sign up to set email alerts
|

Debugging probabilistic programs

Abstract: Many applications compute with estimated and uncertain data. While advances in probabilistic programming help developers build such applications, debugging them remains extremely challenging. New types of errors in probabilistic programs include 1) ignoring dependencies and correlation between random variables and in training data, 2) poorly chosen inference hyper-parameters, and 3) incorrect statistical models. A partial solution to prevent these errors in some languages forbids developers from explicitly inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…We use the Uncertain T programming language to implement random quantization. We choose it, because Uncertain T is sufficiently expressive and automates inference, and thus significantly simplifies our implementation [12], [42], [43]. The remainder of this section gives background on Uncertain T , the programming model that inspired and supports our technique, and describes our implementation.…”
Section: Methodsmentioning
confidence: 99%
“…We use the Uncertain T programming language to implement random quantization. We choose it, because Uncertain T is sufficiently expressive and automates inference, and thus significantly simplifies our implementation [12], [42], [43]. The remainder of this section gives background on Uncertain T , the programming model that inspired and supports our technique, and describes our implementation.…”
Section: Methodsmentioning
confidence: 99%
“…Having defined the statement-level transformations we now state a theorem about T β P [•] preserving continuity. As many applications may invoke inference at any point in the program [46,60], it is important that absolute continuity of each marginal hold at every point.…”
Section: Bringing It All Together: Full Program Transformationsmentioning
confidence: 99%
“…Verification and Analysis of Probabilistic Programs. Previous research proposed various techniques for statically analyzing and verifying properties of probabilistic programs, e.g., [6,11,14,25,31,33,37], including analyses that aim to help with debugging, e.g., [23,38,40]. In comparison, Storm presents a dynamic analysis that performs a heuristic search for smaller probabilistic program that reveal the same bugs.…”
Section: Related Workmentioning
confidence: 99%
“…The numerical and approximate nature of PP systems and implementation complexity make it hard to ensure their correctness, and subtle bugs can easily remain unnoticed [20,38,47]. Our recent study [10] showed that over 25% of all bugs in three popular systems are domain specific, including algorithmic, numerical, boundary condition, dimensional, and accuracy bugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation